Радянське підпілля в Луцьку у 1941–1944 рр. - Zek, Bohdan (Komunizm: System - Ludzie - Dokumentacja, 2015)
The history of Lutsk underground was created in times of USSR, which is widely used with the ideological aim. The main leaders of this organization were V. Izmailov and P. Savelieva. Soviet underground workers helped prisoners of war and carried out scouting and sabotage work. Intensification of their activities came in 1943. At this time Lutsk underground established a link with partisan platoons of D. Medvedev, M. Prokopyuk, A. Brynskyj and others. According to the official Soviet version, P. Savelieva was arrested by the German secret services and burned alive in the yard of Lutsk prison. This episode was quite widely used by Soviet historians and propagandists. After the collapse of the USSR it was found that documents about Lutsk underground actually were not preserved or they were not put to scientific use. New source base makes radically change not only the opinion, but also highlight the quite different story of the Soviet underground in Lutsk during the Nazi occupation.